#TITLE_ALTERNATIVE# - BINTANG SUSETYO ( NIM : 12214058 ), DWI
In this study describes the application of Integrated Capacitance Resistive Model (ICRM) in the waterflood field.ICRM is a new method developed from a Capacitance Resistive Model (CRM) that was proven successfully to evaluate of waterflood field performance. This method uses an analytical approach by integrating continuity material balance equation. The procedure uses linear multivariate regression on production and injection rate. This method can quantify compressible pore volume (the capacitance) and degree of connectivity between wells (the resistance). This Study uses ICRM result to optimize oil production by adjusting water injection rate in real and synthetic fields. Before the optimization, the connection between wells (connectivity) were established by fitting ICRM on cumulative total production is obtained from production data. After the ICRM parameter are obtained, the oil production model is made by fitting the data of oil production rate. Both models are used to perform production optimization by changing the injection rate in some future time. The oil production rate increases after changing allocation of water injection rate based on ICRM result. The advantages of ICRM can decrease the computational time, required data is already available, can be applied for large field with many wells, the result is suitable with geological condition, and the result of parameter model is unique solution because ICRM using linear regression. ICRM can be used to improve oil production easily and with low additional cost.